A general numerical model for simulating the long-term response of two-layer composite systems in partial interaction. (1st February 2021) - Martinelli, Enzo
Abstract: Two-layer composite members are widely employed in structural engineering: composite beams coupling a concrete slab to either a steel joist or a timber beam are probably the most remarkable examples of the aforementioned systems, but also other structural members can somehow be mechanically regarded as two-layer composite systems. Therefore, simulating the long-term behaviour of the aforementioned two-layer composite systems in partial interaction is a relevant and challenging problem, as it depends on both the different long-term response of the two coupled layers and the possible time-dependent behaviour of the interface. In fact, phenomena like creep and shrinkage affect materials in different ways and, hence, a general approach is needed to encompass both the particular kinematic constraints characterising two-layer composite systems in partial interaction and the peculiar behaviour of their materials. The present paper proposes a theoretical formulation and the corresponding numerical implementation of a mechanical model capable of simulating the long-term response of two-layer composite system in partial interaction. A validation of the model is proposed at the end of the paper with respect to experimental results obtained on two different two-layer composite systems reported in the literature. The Python code implemented as part of the present study is available in Open Access to readers.